Chlamydia trachomatis infection and risk of cervical intraepithelial neoplasia. Issue 5 (6th April 2011) - Lehtinen, Matti; Ault, Kevin A; Lyytikainen, Erika; Dillner, Joakim; Garland, Suzanne M; Ferris, Daron G; Koutsky, Laura A; Sings, Heather L; Lu, Shuang; Haupt, Richard M; Paavonen, Jorma; ,
Abstract : Objectives: High-risk human papillomavirus (hrHPV) is the primary cause of cervical cancer. As Chlamydia trachomatis is also linked to cervical cancer, its role as a potential co-factor in the development of cervical intraepithelial neoplasia (CIN) grade 2 or higher was examined. Methods: The placebo arms of two large, multinational, clinical trials of an HPV6/11/16/18 vaccine were combined. A total of 8441 healthy women aged 15–26 years underwent cervicovaginal cytology (Papanicolaou (Pap) testing) sampling and C trachomatis testing at day 1 and every 12 months thereafter for up to 4 years. Protocol-specified guidelines were used to triage participants with Pap abnormalities to colposcopy and definitive therapy. The main outcome measured was CIN. Results: At baseline, 2629 (31.1%) tested positive for hrHPV DNA and 354 (4.2%) tested positive for C trachomatis . Among those with HPV16/18 infection (n=965; 11.4%) or without HPV16/18 infection (n=7382, 87.5%), the hazard ratios (HRs) associated with development of any CIN grade 2 according to baseline C trachomatis status were 1.82 (95% CI: 1.06 to 3.14) and 1.74 (95% CI 1.05 to 2.90), respectively. The results were comparable when only the 12 most common hrHPV infections were considered, but the excess risk disappeared when the outcome was expanded to include CIN grade 3 or worse. Conclusion: Further studies based on larger cohorts with longitudinal follow-up in relation to the C trachomatis acquisition and a thorough evaluation of temporal relationships of infections with hrHPV types, C trachomatis and cervical neoplasia are needed to demonstrate whether and how in some situations C trachomatis sets the stage for cervical carcinogenesis. Trial registration: NCT00092521 and NCT00092534 .